2013
DOI: 10.1371/journal.pone.0083759
|View full text |Cite
|
Sign up to set email alerts
|

Proof of Concept, Randomized, Placebo-Controlled Study of the Effect of Simvastatin on the Course of Age-Related Macular Degeneration

Abstract: BackgroundHMG Co-A reductase inhibitors are ubiquitous in our community yet their potential role in age-related macular degeneration (AMD) remains to be determined.Methodology/Principal Findings Objectives: To evaluate the effect of simvastatin on AMD progression and the effect modification by polymorphism in apolipoprotein E (ApoE) and complement factor H (CFH) genes. Design: A proof of concept double-masked randomized controlled study. Participants: 114 participants aged 53 to 91 years, with either bilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(118 citation statements)
references
References 41 publications
3
100
1
4
Order By: Relevance
“…Perhaps simvastatin and other lipophilic statins should be considered for the effect on the formation, reduction, or removal of drusen, cholesterol-containing deposits (>40%, v/v) appearing with age under the RPE and being a pathologic hallmark of AMD ( 55 ). Combined with the recent investigation showing signifi cant improvements in the ultrastructure and function of the PR/RPE/Bruch's membrane region in the simvastatin-treated mice fed high-fat atherogenic diet ( 56 ), the present work supports the idea of revisiting statins for the treatment or prevention of AMD ( 13,56,57 ). Testing of statins is also warranted by their cholesterol-independent effects ( 58, 59 ), some of which (e.g., improvement of endothelial function, reduction of infl ammation and angiogenesis) could be of therapeutic value for AMD ( 57 ).…”
Section: Discussionsupporting
confidence: 80%
“…Perhaps simvastatin and other lipophilic statins should be considered for the effect on the formation, reduction, or removal of drusen, cholesterol-containing deposits (>40%, v/v) appearing with age under the RPE and being a pathologic hallmark of AMD ( 55 ). Combined with the recent investigation showing signifi cant improvements in the ultrastructure and function of the PR/RPE/Bruch's membrane region in the simvastatin-treated mice fed high-fat atherogenic diet ( 56 ), the present work supports the idea of revisiting statins for the treatment or prevention of AMD ( 13,56,57 ). Testing of statins is also warranted by their cholesterol-independent effects ( 58, 59 ), some of which (e.g., improvement of endothelial function, reduction of infl ammation and angiogenesis) could be of therapeutic value for AMD ( 57 ).…”
Section: Discussionsupporting
confidence: 80%
“…270 Statin therapy has been associated with lower rates of progression of age-related macular degeneration in observational studies, but there is limited evidence from randomized trials to support this apparent protective effect. 271 The refutation of the claims of large effects of statin therapy on cataract, reinforced by the clear lack of effects on more sensitive measures of lens opacities, provides another illustration of how the combination of large size and the inherent biases of non-randomized studies can lead to associations of a treatment with an outcome that may be precise (i.e. involve small random errors) but not causal.…”
Section: Cataract and Other Vision-related Outcomesmentioning
confidence: 99%
“…However, recently a prospective randomized controlled trial has been carried out (114 participants) and demonstrated that the cumulative AMD progression rates were lower in the simvastatin-treated group (54%) than in the placebo group (70%) ( 45 ). The treatment rate reduction was even more signifi cant when the post hoc analysis was stratifi ed by the baseline AMD severity and CFH genotype: >4-fold decrease in people with nonadvanced AMD and >12-fold decrease in carriers of CC (Y402H) CFH ( 45 ). These promising results suggest that statins should be reconsidered as therapeutics for AMD and that recent studies in simvastatin treatment in mice ( 41,42 ) along with the fi ndings of the present work may be of human relevance.…”
Section: Discussionmentioning
confidence: 99%